ACCOUNTING SYSTEM DESIGN FOR THE OPERATION OF RENTAL FLATS AND SPORTS VENUE OF RIAU PROVINCE - salmiah, neneng; Oemar, Fahmi; Farwitawati , Reni (Jurnal Niara, 2019)
The study aimed at conducting an analysis towards the operation of Athlete Homestead for the National Sports Week in 2012 belonging to Riau Province. Regarding the Finance Operation System in the form of Sub-district Development Program-Regional Public Service Agency (PPK BLUD), the researcher designed the Accounting System for the Regional Public Service Agency of the Rental Flats and Sports Venue. The data analysis in this study used the descriptive qualitative method by describing the accounting system design for the operation of Rental Flats and Sports Venue through the Sub-district Development Program-Regional Public Service Agency (PPK BLUD) with the procedure comprising: designing the rent system and procedure of the Rental Flats and Sports Venue, designing the system of cash management from the rent income, implementing focused-group discussion with the related parties and the government, working on the policy improvement draft for the operation of the Rental Flats and Sports Venue belonging to Riau Province.Based on the result of the study and discussion, it can be concluded that in order to improve the effectiveness of the service and operation of Rental Flats and Sports Venue with sound business practice, it is necessary to implement the Finance Operation System in the form of Sub-district Development Program-Regional Public Service Agency (PPK BLUD). The design system of the Sub-district Development Program-Regional Public Service Agency (PPK BLUD) comprising the organization chart, the transaction proof document, and the financial management procedure